ChemInform Abstract: Anionic Ordering in Ba15V12S34O3, Affording Three Oxidation States of Vanadium and a Quasi‐One‐Dimensional Magnetic Lattice. Issue 23 (May 2016) - Wong, Christina Jessica; Hopkins, Emily Jane; Prots, Yurii; Hu, Zhiwei; Kuo, Chang‐Yang; Pi, Tun‐Wen; Valldor, Martin
Abstract: Polycrystalline Ba15 V12 S34 O3 is prepared by solid state reaction of a 12:3:12:22 molar mixture of BaS, BaO, V, and S under 200 mbar Ar (corundum crucible in sealed quartz tube, 1.